2012
DOI: 10.1016/j.forsciint.2012.03.020
|View full text |Cite
|
Sign up to set email alerts
|

Voltammetric determination of Δ9-THC in glassy carbon electrode: An important contribution to forensic electroanalysis

Abstract: A new voltammetric method for the determination of Δ(9)-tetrahydrocannabinol (Δ(9)-THC) is described. The voltammetric experiments were accomplished in N-N dimethylformamide/water (9:1, v/v), using tetrabutylammonium tetrafluoroborate (TBATFB) 0.1mol/L as supporting electrolyte and a glassy carbon disk electrode as the working electrode. The anodic peak current was observed at 0.0V (vs. Ag/AgCl) after a 30s pre-concentration step under an applied potential of -1.2V (vs. Ag/AgCl). A linear dependence of Δ(9)-TH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
28
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(30 citation statements)
references
References 16 publications
1
28
0
Order By: Relevance
“…Balbino et al investigated the electrochemical behavior of delta 9 -tetrahydrocannabinol (Δ 9 -THC), the psychoactive substance in hemp, by cyclic and linear sweep voltammetry using a glassy carbon working electrode [10]. Electrochemical techniques offer several advantages: (i) they are sensitive, accurate, and precise; (ii) they enable one to work with a large range, relative instrumentation and materials; (iii) they can be applied to colored materials and samples containing dispersed solid particles [7,8]; (iv) they provide rapid response; (v) and they allow for analysis of the irreversible electrooxidation of the tertiary amine present in the cocaine molecule [11].…”
Section: Introductionmentioning
confidence: 99%
“…Balbino et al investigated the electrochemical behavior of delta 9 -tetrahydrocannabinol (Δ 9 -THC), the psychoactive substance in hemp, by cyclic and linear sweep voltammetry using a glassy carbon working electrode [10]. Electrochemical techniques offer several advantages: (i) they are sensitive, accurate, and precise; (ii) they enable one to work with a large range, relative instrumentation and materials; (iii) they can be applied to colored materials and samples containing dispersed solid particles [7,8]; (iv) they provide rapid response; (v) and they allow for analysis of the irreversible electrooxidation of the tertiary amine present in the cocaine molecule [11].…”
Section: Introductionmentioning
confidence: 99%
“…The forward and backward components of these responses were similar and indicate an irreversible electrode reaction. It was suggested that the peak of THC originates from the one-electron, one-proton oxidation of the phenol group to form the phenoxy radical [21], as in the case of other phenols [37,38]. The radical generally decays via rapid polymerization [39,40].…”
Section: Methodsmentioning
confidence: 99%
“…The cannabinoids form a group of C 21 terpenophenolic compounds unique to the plant Cannabis sativa L. To date, more than 85 different cannabinoids have been isolated from the cannabis plant. Of these, the most important are: cannabinol (CBN), cannabidiol (CBD) and the psychoactive component delta-9-tetrahydrocannabinol (THC) (see Scheme 1) [1][2][3].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“… 9 -THC can be directly detected by monitoring the anodic peak at 0 V vs Ag/AgCl on a glassy carbon electrode. 18,49,50 This research presented for the first time a direct electrochemical oxidation sensor which could provide meaningful voltammetric signatures for synthetic cannabinoids thus allowing the detection of these NPS in seized materials and biological samples, as shown in Figure 4.…”
mentioning
confidence: 98%